Pengaruh Media Youtube Stand Up Comedy pada Pembelajaran Lawakan Tunggal terhadap Kemampuan Berbicara Kelas X SMKN 7 Semarang - Mila Santika; Arisul Ulumuddin; Sri Kismiyati (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
In the practice of stand up comedy which are carried out in front of the class, there are still many students who are confused in conveying the material that has been written. In the first performance the students expressed more monotonously and it was not seen that the material presented was a form of humor. Students are still confused about starting words, giving facial expressions that match what is said so that other students who watch do not understand the meaning of the humor conveyed. The purpose of this experiment is to find out the effect of YouTube Stand Up Comedy media on learning stand up comedy on the speaking ability of class X SMKN 7 Semarang. Researchers used the experimental method by carrying out the normality test and T test. The average pre-test score was 73.78 and the post-test average score was 80.39. The results of the experiment show that the paired sample t-test table obtained a significance value (2-tailed), namely 0.000 <0.05. From these results, Hypothesis 0 is rejected and Hypothesis a is accepted. The conclusion from the research results is that there is an effect of using YouTube stand up comedy media on learning stand up comedy on the speaking ability of class X SMKN 7 Semarang. Suggestions for further research to optimize the data collection process so that the data obtained is more valid.